Neuromyelitis optica: a case report - Del Carpio Medina, Flor de María Elisa (2021)
The neuromyelitis optica (NMO) or Devic's disease, previously defined by the occurrence of optical neuritis (NO) and transverse myelitis (MT), is currently considered as a spectrum of autoimmune, inflammatory and demyelinating disorders of the CNS. Clinical case: Patient with 2-week clinical history, characterized by abrupt decrease in visual acuity in both eyes, not associated with pain, concomitantly presents decreased sensitivity in the abdominal region and decreased muscle strength in both lower limbs, which make walking impossible. Results: The discovery of the AQP4 autoantibody (anti-AQP4) and its association with NMO, as well as differences in clinical presentation, laboratory, neuroimaging, response to treatment and prognosis, have allowed differentiating this pathology from multiple sclerosis (MS). Conclusion: The prognosis of patients with NMO is discouraging, from the inability to walk unaided, to unilateral or bilateral blindness, can occur in 50 % of cases.